MEDICAL AND PSYCHOLOGICAL ASPECTS OF INFERTILITY - S. V. Apresyan; A. A. Abashidze; V. F. Arakelyan (Акушерство, гинекология и репродукция)
Healthy family is an objective criterion of population health and an assessment indicator of social and economic problems. The fraction of infertile couples in Russian Federation varies between 8% and 17% and currently demonstrates no clear trend towards declining. From a social welfare perspective it has not only physical,  familial or psychological repercussions but also social and demographic consequences.